Reducing salt intake by urine chloride self-measurement in non-compliant patients with chronic kidney disease followed in nephrology clinics: a randomized trial. Issue 7 (8th December 2020) - Panuccio, Vincenzo; Mallamaci, Francesca; Pizzini, Patrizia; Tripepi, Rocco; Garofalo, Carlo; Parlongo, Giovanna; Caridi, Graziella; Provenzano, Michele; Mafrica, Angela; Simone, Giuseppina; Cutrupi, Sebastiano; D'Arrigo, Graziella; et al.
Abstract: Background: Adherence to low salt diets and control of hypertension remain unmet clinical needs in chronic kidney disease (CKD) patients. Methods: We performed a 6-month multicentre randomized trial in non-compliant patients with CKD followed in nephrology clinics testing the effect of self-measurement of urinary chloride (69 patients) as compared with standard care (69 patients) on two primary outcome measures, adherence to a low sodium (Na) diet (<100 mmol/day) as measured by 24-h urine Na (UNa) excretion and 24-h ambulatory blood pressure (ABPM) monitoring. Results: In the whole sample ( N = 138), baseline UNa and 24-h ABPM were143 ± 64 mmol/24 h and 131 ± 18/72 ± 10 mmHg, respectively, and did not differ between the two study arms. Patients in the active arm of the trial used >80% of the chloride strips provided to them at the baseline visit and at follow-up visits. At the third month, UNa was 35 mmol/24 h (95% CI 10.8–58.8 mmol/24 h; P = 0.005) lower in the active arm than the control arm, whereas at 6 months the between-arms difference in UNa decreased and was no longer significant [23 mmol/24 h (95% CI −5.6–50.7); P = 0.11]. The 24-h ABPM changes as well as daytime and night-time BP changes at 3 and 6 months were similar in the two study arms (Month 3, P = 0.69–0.99; Month 6, P = 0.73–0.91). Office BP, the use of antihypertensive drugs, estimated Glomerular Filtration Rate (eGFR) and proteinuria remained unchanged across the trial. Conclusions: The application of self-measurement of urinary chloride to guide adherence to a low salt diet had a modest effect on 24-h UNa and no significant effect on 24-h ABPM. Graphical Abstract: